Visual Awareness of Properties. - KENNEDY, MATTHEW J. (Philosophy & Phenomenological Research, 2007)
I defend a view of the structure of visual property-awareness by considering the phenomenon of perceptual constancy. I argue that visual property-awareness is a three-place relation between a subject, a property, and a manner of presentation. Manners of presentation mediate our visual awareness of properties without being objects of visual awareness themselves. I provide criteria of identity for manners of presentation, and I argue that our ignorance of their intrinsic nature does not compromise the viability of a theory that employs them. In closing, I argue that the proposed manners of presentation are consistent with key direct-realist claims about the structure of visual awareness.